Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1097/bot.0000000000001595
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Significance in Trauma Research: Too Unstable to Trust?

Abstract: Objectives: To evaluate the stability of statistical findings in the fracture care literature based on minor changes in event rates and to determine the utility of applying both the Fragility Index (FI) and Fragility Quotient (FQ) to comparative orthopaedic trauma trials. Methods: All fracture care studies from 1991 to 2013 in the Journal of Bone and Joint Surgery and the Journal of Orthopaedic Trauma were screened. The FI was determined by altering the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
41
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 19 publications
11
41
1
Order By: Relevance
“…For this systematic review, the overall FI was found to be 3.77 and the overall FQ to be 0.040, which are consistent with previous orthopaedic literature reporting an average median FI 12,18,22,23,30,48 of 2.5 and mean FQ 32,48 of 0.031. Our findings demonstrate that statistical significance may be altered by the reversal of \4 outcome events or the reversal of 4% of outcome events.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…For this systematic review, the overall FI was found to be 3.77 and the overall FQ to be 0.040, which are consistent with previous orthopaedic literature reporting an average median FI 12,18,22,23,30,48 of 2.5 and mean FQ 32,48 of 0.031. Our findings demonstrate that statistical significance may be altered by the reversal of \4 outcome events or the reversal of 4% of outcome events.…”
Section: Discussionsupporting
confidence: 89%
“…The authors of a recent evaluation of 20 years of orthopaedic trauma literature recommended ''triple reporting,'' consisting of P values, the FI, and the FQ. 32 Establishing guidelines that encourage the reporting of the FI and FQ together will improve how physicians and surgeons perceive the strength of study findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FI has been applied in review studies of anticancer medicines, clinical heart failure, anesthesiology, and several other areas of study, in order to characterize robustness of results amid concern over reproducibility of research. [2][3][4][5][6][7][8][9][10][11][12][13][14] The Fragility Index has been criticized for using Fisher's exact test as its basis when many trials use survival analysis, which is more powerful than Fisher's exact test and can demonstrate differences in time to event as well as the probability of an event. One review of oncology studies found several trials with P-values <.001 and FI values of zero (implying a P-value >.05 by Fisher's exact test).…”
Section: Introductionmentioning
confidence: 99%
“…As such, at least part of what the index is intended to capture is the fragility of results due to bias from missing data. The FI has been applied in review studies of anticancer medicines, clinical heart failure, anesthesiology, and several other areas of study, in order to characterize robustness of results amid concern over reproducibility of research 2‐14 …”
Section: Introductionmentioning
confidence: 99%